Impact of Population Density on Physical Environmental Quality - Lia Warlina; Nafilah Aulia; Kevin Rizal Lukmanul Hakim; Nuraeni Nuraeni; Natasha Puspa Dewi (Unika Soegijapranata Semarang, 2021)
This study aims to identify and assess population density that causes slums and physical effects on the environment in the Simpang Dago area. The methodology used is a qualitative research method on the object's condition by conducting a literature study and collecting related documents. The study was conducted with a case study in one area in the city of Bandung. The results showed that the achievement of comfort, safety, health, and mutual satisfaction is expected to help reduce population density impact in the Simpang Dago area. To achieve that goal, a study of population density impact on the quality of the physical environment. The solution of densely populated areas problem by relocating residents and providing affordable vertical housing by considering various aspects. The implication of this study's results is due to the dense population and houses' distance is too close; therefore residents around the Simpang Dago area must be concerned about their environment's cleanliness. In addition, not all population density gives negative impacts to the quality of an area's physical environment, depending on the residents' awareness.